Kesenjangan Upah dan Keadilan Sosial terhadap Sistem Pengupahan di Indonesia - Indrayani, Sufi; Muzan, Amrul (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
Wage disparity in Indonesia reflects a significant challenge in social justice, particularly within the wage system. This study aims to identify and analyze the factors contributing to wage inequity, including policies, corporate practices, and gender and sectoral inequalities. Using a qualitative approach, the study explores perspectives from various stakeholders, such as workers, employers, and regulators, while utilizing policy data and relevant documents for analysis. The findings reveal that structural injustices in wage distribution have widened the gap between high- and low-income workers. Factors such as differences in education, experience, and geographic location significantly contribute to this disparity. Gender-based inequality is also a major concern, with women often receiving lower wages than men despite having equivalent qualifications. In terms of policy, the study found that minimum wage regulations are often insufficient to address these inequalities. A lack of transparency in wage determination and weak regulatory enforcement exacerbate the issue. Theoretical frameworks, such as John Rawls' theory of justice, emphasize the importance of redistributing wages to benefit the most disadvantaged groups, while the efficiency wage theory suggests that higher wages can enhance worker productivity. This study recommends reforms in wage policies focused on distributive justice, increased transparency, and strengthened government regulations. These approaches are expected to create a more inclusive wage system that considers not only economic aspects but also social welfare, fostering sustainable social and economic stability in Indonesia.